Why Was the Official Australian Monsoon Onset Unusually Late in 2024/25? - Tim Cowan; Rajashree Naha; Hanh Nguyen; Hanna Heidemann; Sugata Narsey; Matthew C. Wheeler; Corey Robinson; Chris Lucas; Andrew G. Marshall; Lin Wang (Advances in Atmospheric Sciences, 2026)
The official 2024/25 Australian summer monsoon (ASM) onset occurred on 7 February, more than two weeks later than the previous record. Defined using Darwin winds, the official ASM typically arrives between mid-December and mid-January. Here, we investigate (1) why the ASM onset was record late, despite La Niña-like conditions, and (2) if the late ASM onset was consistent with other unofficial monsoon and rainy season onset definitions. Our results show earlier onsets when using wind and rainfall-based definitions, mainly due to strong synoptic-to-intraseasonal variability. Two onset definitions were triggered in December 2024 when the Madden–Julian Oscillation (MJO) contributed to deep convection and above-average rain over northern Australia. In late January, a monsoon trough formed over northeast and northwest Australia, but not over Darwin. With the MJO in a suppressed state, the Darwin region experienced record-breaking January temperatures. The ASM eventually arrived in early February, with the reason behind its historically late onset likely a result of weather noise and variability. Another location, ∼1200 km east of Darwin, did not experience such a late onset, using similar definitions. Relevant to monsoon systems globally, our study highlights the limitations of local onset or wind-only definitions, which may not necessarily capture the large-scale monsoonal conditions, and be amplified by short-term weather variability.

Exploring the green break of season and green date over northern Australia - Rajashree Naha; Tim Cowan; Matthew C. Wheeler; Jyoteshna Owens; David Cobon; Chelsea Jarvis; Peter O’Reagain (Agricultural Systems, 2026)

Deep-sea biotope classification using opportunistic sampling: insights for future management - Heidy Q. Dias; Kerstin Kröger; Andrew J. Wheeler; Riccardo Arosio; Audrey Recouvreur; Tim P. Le Bas; Isobel A. Yeo; Patrick C. Collins (Deep Sea Research Part I: Oceanographic Research Papers, 2025)

Taxonomic reintroduction of the holarctic saprotrophic fungus Crepidotus cinnamomeus - Soňa Jančovičová; Katarína Adamčíková; Miroslav Caboň; Mary G. Graddy; P. Brandon Matheny; Chance R. Noffsinger; Tim B. Wheeler; Slavomír Adamčík (Mycological Progress, 2024)
Crepidotus is a genus of common saprotrophic fungi well known especially in the Northern Hemisphere, but distribution patterns of individual species are not sufficiently understood. We redefined a taxonomic circumscription of Crepidotus cinnamomeus based on morphological and molecular congruencies between the type material and recent collections. The species is well delimited from other similar and currently accepted species of the genus. Crepidotus cinnamomeus was found to have a broad holarctic distribution with occurrences in North America, Europe and Asia where it grows on twigs and branches of deciduous trees and shrubs in preferably cold humid habitats. Here we present the first multilocus phylogeny of the genus, including portions of the RPB2 gene. Our study highlights the importance of sufficient sampling from broader areas supported by sequence data, which is essential for estimation of species delimitation, distribution and correct name assignment for Crepidotus species.

Rural household vulnerability to climate risk in Uganda - Sarah Jane Cooper; Tim Wheeler (Regional Environmental Change, 2017)

Impact of progressive global warming on the global-scale yield of maize and soybean - Gillian Rose; Tom Osborne; Helen Greatrex; Tim Wheeler (Climatic Change, 2016)

Assessing the vulnerability of food crop systems in Africa to climate change - Andrew Challinor; Tim Wheeler; Chris Garforth; Peter Craufurd; Amir Kassam (Climatic Change, 2007)

Development and assessment of a coupled crop–climate model - TOM M. OSBORNE; DAVID M LAWRENCE; ANDREW J. CHALLINOR; JULIA M. SLINGO; TIM R. WHEELER (Global Change Biology, 2007)
It is well established that crop production is inherently vulnerable to variations in the weather and climate. More recently the influence of vegetation on the state of the atmosphere has been recognized. The seasonal growth of crops can influence the atmosphere and have local impacts on the weather, which in turn affects the rate of seasonal crop growth and development. Considering the coupled nature of the crop–climate system, and the fact that a significant proportion of land is devoted to the cultivation of crops, important interactions may be missed when studying crops and the climate system in isolation, particularly in the context of land use and climate change. To represent the two‐way interactions between seasonal crop growth and atmospheric variability, we integrate a crop model developed specifically to operate at large spatial scales (General Large Area Model for annual crops) into the land surface component of a global climate model (GCM; HadAM3). In the new coupled crop–climate model, the simulated environment (atmosphere and soil states) influences growth and development of the crop, while simultaneously the temporal variations in crop leaf area and height across its growing season alter the characteristics of the land surface that are important determinants of surface fluxes of heat and moisture, as well as other aspects of the land‐surface hydrological cycle. The coupled model realistically simulates the seasonal growth of a summer annual crop in response to the GCM's simulated weather and climate. The model also reproduces the observed relationship between seasonal rainfall and crop yield. The integration of a large‐scale single crop model into a GCM, as described here, represents a first step towards the development of fully coupled crop and climate models. Future development priorities and challenges related to coupling crop and climate models are discussed.